Minimally Invasive Video-Assisted Thyroidectomy: Analysis of Complications From a Systematic Review. (June 2019) - Scerrino, Gregorio; Melfa, Giuseppina; Raspanti, Cristina; Rotolo, Giulia; Salamone, Giuseppe; Licari, Leo; Fontana, Tommaso; Tutino, Roberta; Porrello, Calogero; Gulotta, Gaspare; Cocorullo, Gianfranco
Background . Nowadays, minimally invasive video-assisted thyroidectomy (MIVAT) is considered a safe and effective option. However, its complication rate has not been specifically discussed yet. The aim of this systematic review was enrolling a large number of studies to estimate early and late complications (transient and definitive, uni- and bilateral laryngeal nerve palsy; transient and definitive hypocalcemia; cervical hematoma; hypertrophic or keloid scar) of MIVAT compared with conventional technique. Methods . The review was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria in PubMed and Embase. Search terms were "minimally invasive, " "video-assisted, " and "thyroidectomy." We enrolled randomized clinical trials, nonrandomized trials, and noncontrolled trials. Results . Thirty-two articles were considered suitable. Complication rate of MIVAT was quite similar to conventional technique: only one randomized trial found a significant difference concerning overall skin complication, and a single trial highlighted hypocalcemia significantly increased in MIVAT, concerning serologic value only. No difference concerning symptomatic nor definitive hypocalcemia was found. Conclusions . We can confirm that MIVAT is a safe technique. It should be adopted in mean-high-volume surgery centers for thyroidectomy, if a strict compliance with indication was applied.